The role of radiographers in ultrasound: A survey of the national societies within the European Federation of Radiographer Societies (EFRS). Issue 3 (August 2021) - Harrison, G.; Kraus, B.; Martins Dos Santos, R.; Noij-Rijkes, S.; Pedersen, M.R.V.
Abstract: Introduction: Ultrasound is one of many areas of specialism for radiographers to develop their skills in. As part of a wider suite of surveys, the European Federation of Radiographer Societies (EFRS) wanted to investigate the extent and scope of practice for radiographers practising ultrasound across Europe. This report details the results of the initial survey, exploring the views of the EFRS countries' National Radiographer Societies. Methods: An electronic survey was sent to representatives of the 43 national radiographer societies who were members of the EFRS. Questions asked about radiographer practice in ultrasound within individual countries, scope of the role, particularly report writing, in addition to investigating current ultrasound education, barriers and opinions on priorities for radiographer ultrasound practice. Results: Forty individual responses were received, from a total of 27 countries, covering 62.8% of the EFRS member societies invited to participate. Radiologists or specialised medical practitioners performed ultrasound in the majority of countries. Radiographers practise ultrasound in 48% of countries and 11% have some limited involvement in ultrasound. Countries without radiographer engagement in ultrasound reported legislative issues or lack of acceptance from the medical professions (52%) and/or limited specific ultrasound education (39%) as predominant factors. In most countries where radiographers practise ultrasound, clinical reporting is a descriptive report or checklist approved by a medical doctor/radiologist. Conclusion: The results highlight the scope of practice and barriers faced in some EFRS countries to enabling radiographers to develop their skills and competencies in ultrasound. Implications for practice: Priorities for radiographer societies to assist in the development of ultrasound as a pathway for radiographer progression in countries, where it is not yet available, include education programmes, acceptance by medical professionals and changes to legislation.